Efeitos de ações antrópicas sobre as interações bióticas entre os peixes de uma planície de inundação Neotropical: alterações nos padrões de coocorrência de espécies. - Andreotti, Gustavo Faccin (2024)
The freshwater ichthyofauna is largely threatened by the anthropogenic impacts in these ecosystems. The climatic changes caused by human actions and dams’ constructions concerningly affects the freshwater fishes, including its biotic interactions network. Thus, this work aimed at evaluating the Upper Paraná River floodplain’s (UPRF) ichthyofauna under the impacts caused by climate changes, years of extreme drought an extreme flood, and under the impacts caused by the construction of an upstream dam, the Sérgio Motta Hydroelectric Power Plant, Brazil. The sampled years were classified in extreme drought, neutral and extreme flood, according to the predominant characteristics of its hydrological regime, and in pré-damming years, before the upstream hydroelectric power plant construction and reservoir’s flooding, and post-damming years. The abiotic and hydrometric variables were concurrently sampled with the abundance of fish species, allowing to exclude the environmental variables’ effects over the species’ cooccurrence, using multivariate generalized linear models with latent variables. The force of the interspecific biotic interactions was obtained through cooccurrence values for each pair of species, visualized through negative, neutral, and positive values. Regarding the results involving the hydrological regime influence, it was observed differences between drought, neutral and flood years, with stronger cooccurrence values between the UPRF’s ichthyofauna in drought years (for positive and negative values). Regarding the results involving the construction of the UPRF’s upstream dam, it was observed differences comparing the pré-damming and post-damming years cooccurrence patters, with predominantly positive values in post-damming years, and predominantly neutral cooccurrences in pré-damming years. These work results indicate the increment of the cooccurrence values between a floodplain’s fish species due to extreme droughts and upstream dams’ constructions, once the cooccurrence values were more intense under these conditions. Stands out the importance of biotic interactions for the elaboration of management plans and freshwater species conservation in response to anthropogenic actions.